2016
DOI: 10.1093/gastro/gow031
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Doppler ultrasonography for predicting improvement of platelet count after transjugular intrahepatic portosystemic shunt

Abstract: ObjectivePortal pressure gradient (PPG) after transjugular intrahepatic portosystemic shunt (TIPS) <12 mmHg has been reported as the only factor predictive of increase in platelet count. As flow velocities measured on Doppler ultrasound are related to pressure gradient based on the Bernoulli equation, we used this parameter to predict increased platelet count after TIPS placement.MethodsA total of 161 consecutive patients who underwent TIPS placement entered this retrospective study. The platelet count was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Indeed, if the portosystemic gradient after TIPS remains high, the platelet count does not increase. [160] Some studies found no significant increase in platelet count in patients with cirrhosis undergoing TIPS. [161][162][163] Notably, TIPS is not primarily indicated for the treatment of low platelet count but only for complications of portal hypertension.…”
Section: Radiological Interventions To Treat Hypersplenism In Patient...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if the portosystemic gradient after TIPS remains high, the platelet count does not increase. [160] Some studies found no significant increase in platelet count in patients with cirrhosis undergoing TIPS. [161][162][163] Notably, TIPS is not primarily indicated for the treatment of low platelet count but only for complications of portal hypertension.…”
Section: Radiological Interventions To Treat Hypersplenism In Patient...mentioning
confidence: 99%
“…However, the rise in platelet count is generally mild (20%–25% than baseline) 159 and occurs as early as 1 week after the TIPS, 157 which likely reflects the reduced splenic sequestration. Indeed, if the portosystemic gradient after TIPS remains high, the platelet count does not increase 160 . Some studies found no significant increase in platelet count in patients with cirrhosis undergoing TIPS 161–163 .…”
Section: Thrombocytopenia In Patients With Cirrhosis: Definition Path...mentioning
confidence: 99%
“…While decompression of PH by TIPS might ameliorate inflammation in some patients (by limiting bacterial translocation) and reduce splanchnic venous vascular shear stress [ 42 ], some patients do experience a further increase in splenic stiffness (which is considered a marker for portal hypertension and inflammation) after TIPS that is associated with poor post-procedural outcome and increased mortality [ 46 ]. Additionally, mechanical hemolysis of erythrocytes and platelets may impede hematologic improvement or actually worsen blood cell counts in patients undergoing TIPS, as was demonstrated by Ansari-Gilani et al [ 47 ] who reported improvement in platelet counts only in patients with G2-3 thrombocytopenia and patent TIPS according to Doppler sonography. Mechanical destruction of blood cells could be the cause for the decline in blood cell counts in our patients without apparent hematologic hypersplenism (i.e., no or G1 cytopenias).…”
Section: Discussionmentioning
confidence: 99%